2020
DOI: 10.1017/s0305741020000740
|View full text |Cite
|
Sign up to set email alerts
|

“Detaching” Courts from Local Politics? Assessing the Judicial Centralization Reforms in China

Abstract: Abstract The local party-state has always been a major source of extrajudicial influence in China. Drawing on interviews with judges, this article examines the impact of Xi Jinping's ambitious judicial centralization reforms, which are aimed at enhancing judicial autonomy by transferring authority over local court personnel and finances from local to provincial level. It finds that the reforms have achieved limited results. Although many appointment and budgetary powers were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Despite such efforts, however, the procuratorates' status as relatively weak institutions within the party‐state structure remains inherently limiting when it comes to holding government agencies accountable. Studies show that China's recent judicial centralization reforms that aimed to “detach” courts from local governments had limited effect due to regional differences, informal relationships with local agencies, and the influence of local party committees (He, 2020; Wang, 2021). Similar limits apply to the procuratorates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite such efforts, however, the procuratorates' status as relatively weak institutions within the party‐state structure remains inherently limiting when it comes to holding government agencies accountable. Studies show that China's recent judicial centralization reforms that aimed to “detach” courts from local governments had limited effect due to regional differences, informal relationships with local agencies, and the influence of local party committees (He, 2020; Wang, 2021). Similar limits apply to the procuratorates.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some scholars recognize that certain top‐down reforms may enable judicial institutions to move more boldly against powerful local entities. For instance, the judicial centralization reform shifted substantial personnel and budgetary powers over local courts and procuratorates from the local party‐state to the provincial level, thereby decreasing judicial institutions' dependence on localities (Liu et al, 2022; Wang, 2021). Along similar lines, the judicial responsibility reform removed the requirement that court judgments be approved by court leadership before being published, thus reducing the likelihood of outside interference in cases concerning local interests (He, 2020; Wang, 2020a).…”
Section: Judicial Expansion Under Democracy and Authoritarianismmentioning
confidence: 99%
“…UN research has pointed out that as with many of China's reforms, the institutional design of in situ urbanization in China has been largely top-down and led by the central government [35]. Empirical research has shown that the top-down reform model in China has several general limitations, such as authorityresponsibility distribution and fiscal dilemmas [44][45][46][47]. Political economy usually develops institutional analysis from the conceptual framework of endogenous and exogenous causes.…”
Section: Dilemmas and Risks Of In Situ Urbanization 20mentioning
confidence: 99%
“…Legal federalism observed in China (Qiao, 2018;Wang, 2021), as an expression of the inconsistency between the interests of national and local legislators, is internalized into the…”
Section: An Inconsistent and Diverging Legal Framework For The Employ...mentioning
confidence: 99%
“…Legal federalism observed in China (Qiao, 2018; Wang, 2021), as an expression of the inconsistency between the interests of national and local legislators, is internalized into the Chinese legislative mechanism. The same labor legal standard is implemented differently in different provinces or cities, which is related to the level of local economic development and the degree of internationalization.…”
Section: An Inconsistent and Diverging Legal Framework For The Employ...mentioning
confidence: 99%